STIGMA AVOIDANCE AND ONTOLOGICAL SECURITY: INDONESIA’S RESPONSE TO THE EU RED II ON PALM OIL - Pradana, Hafid Adim; Assyifa, Arsya Rahma Nur; Mubin, Sayyidul (International Journal of Cultural and Social Science, 2025)
The European Union’s Renewable Energy Directive II (EU RED II) excluded palm oil as a sustainable feedstock, indirectly stigmatizing Indonesia as a driver of deforestation. This study analyzes Indonesia’s response through the lens of stigma politics and ontological security. Unlike previous research that focused on material-economic impacts, this article highlights identity preservation and stigma avoidance. Using a qualitative case study and interpretive analysis of policy documents, official statements, and media coverage, the study finds that Indonesia’s strategy reflects stigma avoidance: accepting global sustainability norms while rejecting the negative label. This is demonstrated by its World Trade Organization (WTO) lawsuit against the EU, promotion of the Indonesian Sustainable Palm Oil (ISPO) certification, and cooperation with fellow producers through the Council of Palm Oil Producing Countries (CPOPC). The study contributes by conceptualizing stigma avoidance as a narrative-based diplomatic practice through which Indonesia safeguards both material interests and ontological security.